2019
DOI: 10.1088/1757-899x/620/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crushed stone waste as fine aggregate on mortar and concrete properties

Abstract: In this study, effects of crushed stone waste from Katunun’s quarry as fine aggregate on mortar and concrete properties will be examined. Samples with varying crushed stone waste replacement ratio, ranging between 0% until 100%, will be analysed at 3, 7 and 28 days curing time. Mortar sample is using 0.5 w/c ratio, while concrete sample is using 0.45 w/c ratio. The mixture of mortar sample is based on SNI 03-6825-2002, whilst concrete sample is based on SNI 03-2834-2000. The examination of concrete samples wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…In order to avoid this, it is necessary to select the appropriate w/c ratio in mortars with recycled aggregate or to use suitable fluidizing admixtures. The positive effect of recycled aggregate on the strength of cement mortars and concretes has been confirmed by many studies available in the literature [43,[49][50][51][52]. Pavlik et al [43] observed that replacing 25% of natural sand with sandstone aggregate increased the compressive and bending strength of mortars by 15 and 4 (%), respectively, compared to the reference samples.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…In order to avoid this, it is necessary to select the appropriate w/c ratio in mortars with recycled aggregate or to use suitable fluidizing admixtures. The positive effect of recycled aggregate on the strength of cement mortars and concretes has been confirmed by many studies available in the literature [43,[49][50][51][52]. Pavlik et al [43] observed that replacing 25% of natural sand with sandstone aggregate increased the compressive and bending strength of mortars by 15 and 4 (%), respectively, compared to the reference samples.…”
Section: Resultsmentioning
confidence: 78%
“…The authors attributed the increase in strength to a favorable hydration mechanism by creating a homogeneous and dense matrix structure between the aggregate and the slurry. On the other hand, the Prasetia-Maulan team [52] reported that the compressive strength of the mortar measured after 28 days increased along with the amount of waste. The complete replacement of natural river sand with stone waste at a w/c ratio of 0.5 increased the average compressive strength by as much as 80% compared to the sample without waste aggregate.…”
Section: Resultsmentioning
confidence: 99%
“…У сучасних європейських стандартах форму зерен оцінюють за «індексом форми», тобто за середнім відношенням найбільшого й найменшого розмірів зерен проби [31,32]. Таке оцінювання дає можливість робити висновки про форму усієї маси зерен щебеню.…”
Section: рис 1 номенклатура гранітної продукціїunclassified
“…Many studies have found that industrial waste can be used as cement or aggregate substitutes [3]- [8]. It has been reported that this waste is compatible as a substitute for cement and aggregate and gives sufficient and even greater compressive strength of concrete [9]- [13]. Moreover, utilizing this waste as a building material is not only for producing concrete but also for mortar, pavements, soil stabilization, etc.…”
Section: Introductionmentioning
confidence: 99%